Transformasi Ekopedagogi Kristen melalui Ekoteologi dalam Kurikulum untuk Kesadaran dan Mitigasi Pemanasan Global - Zalukhu, Amirrudin (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2025)
Global warming is a serious challenge that demands collective awareness and action, including in the field of education. Christian ecopedagogy, which integrates theological values with environmental concern, plays a crucial role in fostering ecological awareness and promoting global warming mitigation. Transforming ecopedagogy through ecotheology in the Christian education curriculum can strengthen students' understanding of their spiritual responsibility toward nature as part of their faith. By implementing a holistic approach that encompasses theological studies, environmental ethics, and sustainable practices, Christian schools can become agents of change in shaping a generation that is more environmentally conscious. This ecotheology-based learning model can be realized through curriculum integration, real-world action projects, and the active involvement of communities and churches in environmental education. Thus, Christian education not only focuses on academic excellence but also on shaping ecological character rooted in faith-based values to address global environmental challenges.